Development of preplaced aggregate concrete with low cement content - Ghimire, Subarna; Krishna, Chaitanya; Thanakorn Pheeraphan; Pennung Warnitchai; Raktipong Sahamitmongkol; AIT Scholarships (Pathum Thani, Thailand : Asian Institute of Technology, 2023)
When Preplaced Aggregate Concrete (PAC) is cast, coarse aggregates are first preplaced into the formwork, and then grouts are added to fill in the spaces left by the coarse aggregates. This allows coarse aggregates to occupy a significantly larger volume than with traditional casting techniques. This technique mostly depends on the grout's capacity to fill voids and the size of those voids, both of which depend on the workability of the grout and the form and gradation of the coarse aggregate. This research study intended to develop the Preplaced Aggregate Concrete with low cement content. The purpose of this work is to create the optimal mix of PAC with low cement content that can be utilized for specific applications. The use of larger size of fine aggregates into the molds along with coarse aggregates to reduce the void content is also implemented. By doing so, the void content has been reduced from 40 to 37.5%. For further reduction of cement content, supplementary cementitious materials (SCMs) like fly ash (20 to 40%) and silica fume (5 to 7.5%) are used into the grout. Three factor two-level central composite design is setup using Design of Experiment to study the effects of SCMs in PAC. Compressive strength of 39.53 MPa and Flexural strength of 7.95 MPa was the highest value achieved at 28 days. For the maximum replacement of cement, the compressive strength and flexural strength were 26 MPa and 4.24 MPa respectively. Additionally, all the mixes underwent tests for shrinkage and rapid chloride penetration, with excellent outcomes. Fly ash to Binder ratio had negative effect on the compressive and flexural strength but it showed positive response for resisting the chloride ion penetration through the concrete. Shrinkage of the Preplaced aggregate concrete with low cement content was mostly affected by the silica fume to binder ratio.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Structural Engineering
Thesis (M. Eng.) - Asian Institute of Technology, 2023
Keywords: Frost resistant concrete; Aggregates (Building materials)